Evaluation of serum concentrations of the selected cytokines in patients with localized scleroderma - Budzyńska-Włodarczyk, Jolanta; Michalska-Jakubus, Małgorzata M.; Kowal, Małgorzata; Krasowska, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Localized scleroderma is an autoimmune disease primarily affecting the skin. The cause of disease remains unexplained although environmental factors are implicated, which are likely to be responsible for activation of the endothelium and subsequent inflammation leading to excessive synthesis of collagen and extracellular matrix components. Aim: To determine concentrations of interleukin (IL)-27, transforming growth factor (TGF)-β1, TGF-β2, IL-6, and sIL-6R in patients with localized scleroderma compared to controls and to assess the relations between their levels and laboratory markers. Material and methods: The study encompassed 17 females with localized scleroderma (aged 25–67). The control group consisted of 30 age-matched healthy women. The blood was sampled from the basilic vein. Serum levels of cytokines were determined using ELISA. Results : The TGF-β2 levels were found to be significantly lower in patients with localized scleroderma compared to controls. Concentrations of TGF-β1 were decreased in scleroderma patients when compared to controls but without statistical significance. There were no significant differences in serum IL-6, sIL-6R and IL-27 levels between patients and the control group; however, we found a significant positive correlation between the level of sIL-6 and ESR among subjects with localized scleroderma. Conclusions : The findings of decreased serum levels of TGF-β1 and TGF-β2 in patients with localized scleroderma demonstrate a possible association of these cytokines with pathogenesis of the disease. The results suggest also that sIL-6R is likely to be involved in inflammation in patients with localized scleroderma.